Age‐specific responses to spring temperature in a migratory songbird: older females attempt more broods in warmer springs. Issue 10 (13th August 2013) - Bulluck, L.; Huber, S.; Viverette, C.; Blem, C.
Abstract: Increasing global temperature has led to an interest in plasticity in the timing of annual events; however, little is known about the demographic consequences of changing phenology. Annual reproductive success varies significantly among individuals within a population, and some of that variation has to do with the number of broods attempted by reproducing adults. In birds, female age and the timing of reproduction are often predictors of multiple breeding. We hypothesize that double brooding rates may be affected by spring temperature and that the response may vary with female age. We used a long‐term reproductive data set for a migratory songbird, the prothonotary warbler ( Protonotaria citrea ) to assess which factors influence (a) an individual female's probability of double brooding and (b) the annual variation in population‐level double brooding rates. We found that older and earlier nesting birds are more likely to double brood, and that there is no evidence for senescence with regard to this trait such that the oldest females were most likely to double brood. Previous experience with double brooding (i.e., whether the female double brooded in the previous year) significantly increased the probability of doing so again. When assessing annual variation in the double brooding rate, we found an interaction between spring temperature and the proportion of older females in the population. Specifically, older females are more likely to double brood in years with warmer springs, but this relationship was not seen for younger females. Previous studies have shown that warmer temperatures lead to earlier and narrower peaks in resources and we hypothesize that these peaks are more available to older and earlier arriving females, enabling them to successfully raise more than one brood in a season. Understanding how different age classes respond to changing environmental conditions will be imperative to managing declining species. Abstract : We used a long‐term reproductive data set for a migratory songbird, the prothonotary warbler ( Protonotaria citrea ) to assess which factors influence (a) an individual female's probability of double brooding and (b) the annual variation in population‐level double brooding rates. We found that older and earlier nesting birds are more likely to double brood and previous experience (i.e., whether the female double brooded in the previous year) significantly increased the probability of doing so again. When assessing annual variation in double brooding rate, we found that older females are more likely to double brood in years with warmer springs, but this relationship was not seen for younger females.